ROMAN POTTERY FROM A CISTERN IN PANTIKAPAION - Zhuravlev, Denis (Rei Cretariae Romanae Fautorum Acta, 2024)
Recent excavations in Pantikapaion under the auspices of the Pushkin State Museum of Fine Arts, Moscow discovered many interesting contexts of the Roman period. Exploration of the cistern no. 145 was conducted in 1990 and 1999. The cistern represents a monumental rectangular construction with its sides oriented to the north, south, east, and west. The northern side of the reservoir is 4.56 m long, the southern - 4.52 m; the western and eastern sides are 3.90 and 3.80 m respectively. The maximum preserved depth of the cistern in the north-eastern corner is 3.7 m from the floor to the top of the wall.